Evaluasi Metode Health Index Untuk Menentukan Prioritas Pemeliharaan Gardu Distribusi - Galuh Prawestri Citra Handani; Rahman Azis Prasojo; Muhammad Fahmi Hakim; Muhammad Ridlo Zainal; Imron Ridzki; Bustani Hadi Wijaya (Elposys: Jurnal Sistem Kelistrikan, 2024)
Electricity is an essential energy source that plays a crucial role in human life. A key component of power distribution systems is the distribution substation. As distribution substations are in operation over time, their components experience aging, which can result in operational failures. This situation emphasizes the necessity for regular evaluations and diagnostics of distribution substations. Such assessments are crucial for identifying when equipment requires repair or replacement, ensuring that the system operates at maximum efficiency. By implementing a proactive maintenance strategy, utilities can mitigate risks, enhance reliability, and extend the lifespan of their infrastructure. The scoring matrix method is a technique for evaluating the condition of distribution substations. It combines results from field and laboratory tests to produce values that accurately reflect the substation's condition. The research focused on four distribution substations managed by PT PLN, classifying them into high, medium, and low categories based on their health index scores. The results show that, among the four distribution substations evaluated, substations A and C received health indices exceeding 80%, classifying them in the high category. It is therefore recommended that these substations continue operating normally while adhering to their scheduled periodic maintenance. In contrast, substation B received a health index between 50% and 80%, placing it in the medium category. While it can remain operational, it requires closer monitoring and maintenance at specific intervals to ensure reliability and prevent potential issues.